Radiographic Study of Developmental Alteration in Tooth Number among Children in IIUM Dental Clinic - Sukmasari, Susi; Ismail, Nabilahuda; Azaldin, Nurul H; Ardini, Yunita D (Makara Journal of Health Research, 2016)
Background: The aim of this research was to determine the prevalence, distribution and association of developmental alteration in tooth number with gender, location, and presence of delayed eruption of tooth among children who attended to Student's polyclinic of IIUM Kuantan, Malaysia. Methods: A cross sectional study on total 727 Orthopanthomograms (OPGs) of 3-17 years old children from April 2009 to July 2012. OPGs with presence of alteration number were scrutinized to find out the prevalence, distribution and association. The data was analyzed comparing gender, location and presence of delayed eruption and tested using Chi-square test. Results: Out of 727 OPGs, 71 OPGs showed developmental alteration in tooth number. The prevalence was 98/1000 OPGs within 3 years. Among those 71 OPGs, the gender differences were: males (49.3%) and females (50.7%). Locations were found in maxilla (45.1%), mandible (40.8%) and both (14.0%). The finding of delayed eruption was (7.0%). There were significant differences between alteration in tooth number with location as (p < 0.05) while there were no significant differences with gender and delayed eruption as (p > 0.05). Conclusions: This study showed that hyperdontia was considerably lower than hypodontia. There was association between alteration in tooth number with location, but no association with gender and delayed eruption.